2007
DOI: 10.1194/jlr.m700378-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 26 distinct acyl-coenzyme A synthetase genes in the human genome

Abstract: Acyl-coenzyme A synthetases (ACSs) catalyze the fundamental, initial reaction in fatty acid metabolism. "Activation" of fatty acids by thioesterification to CoA allows their participation in both anabolic and catabolic pathways. The availability of the sequenced human genome has facilitated the investigation of the number of ACS genes present. Using two conserved amino acid sequence motifs to probe human DNA databases, 26 ACS family genes/proteins were identified. ACS activity in either humans or rodents was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
337
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(342 citation statements)
references
References 59 publications
5
337
0
Order By: Relevance
“…The difference between the v1 and v2 isoforms resides in their N-termini. The N-terminus of ACSL4 v1 is 41 amino acids shorter than that of v2 [7].…”
Section: H]dhs Labelingmentioning
confidence: 96%
See 3 more Smart Citations
“…The difference between the v1 and v2 isoforms resides in their N-termini. The N-terminus of ACSL4 v1 is 41 amino acids shorter than that of v2 [7].…”
Section: H]dhs Labelingmentioning
confidence: 96%
“…Therefore, ACSs responsible for S1P metabolism should also be localized in the ER for efficient metabolic flow. It has been reported that each ACS isozyme exhibits characteristic intracellular localization, such as in the ER, plasma membrane, mitochondria, and peroxisome [7,13,14]. However, the precise localization of most ACS isozymes remains unclear since inconsistent localization patterns have been reported among researchers using different approaches.…”
Section: H]dhs Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-chain fatty acids are esterified to CoA esters in the inner surface of the plasma membrane before entering intracellular metabolic pathways. Activation of fatty acids occurs primarily via an ATP-dependent mechanism involving the action of ACSL isoforms (Watkins et al, 2007). Measurements in lactating cows have shown that several ACSL (ACSL1, 3, 4 and 5) and FABP (FABP 1,3,4,5 and 6) isoforms are transcribed in mammary tissue (Bionaz and Loor, 2008a) and demonstrated that the expression of ACSL1, FABP3, FABP4 and FABP5 increases several-fold during lactation, whereas changes in the relative abundance of ACBP mRNA are much lower suggesting a minor role in mammary lipogenesis in the bovine (Bionaz and Loor 2008b).…”
Section: Mammary Lipogenesismentioning
confidence: 99%